Treatment paradigm shifting implications of recent cardiovascular outcome trials: Core insights on the brink of the 2020ies. (March 2020) - Standl, Eberhard; Schnell, Oliver
Abstract: Based on cardiovascular (CV) outcome trials (CVOTs) being available on the brink of the 2020ies, CV safety assessed by major adverse CV event outcomes has been established for the classes of glucagon-like-peptide-1 receptor agonists (GLP1 RAs), sodium-glucose-co-transporter-2 inhibitors (SGLT2-is), and dipeptidyl-peptidase-4 inhibitors (DPP4is) in patients at very high CV risk. This should be relevant to the whole population with diabetes in general as well as the fact that no new serious and unexpected side effects have emerged within these trials. At the same time, treatment paradigm shifting CV benefit has been confirmed for two classes of diabetes medications (SGLT2is & GLP1 RAs), with important additional benefit of SGLT2is reducing heart failure and hard renal endpoints, both in patients with such diseases, but also in patients being in primary prevention. Moreover, the "soft" renal outcome of albuminurea progression seems to be attenuated by all three classes of drugs discussed in this overview. Still ongoing CVOTs are not expected to essentially change the current notions, with the potential of some differentiation regarding subgroups of primary heart failure populations in relation to treatment with SGLT2is.